Tathbiq wasilah strip story li tahsini maharah al-kalam li thalibaat as-shaf al-asyir - fajriani, madina; Rukman AR Said; Mubasyyirah Bakri (Institut Agama Islam Negeri (IAIN) Palopo, 2022)
This research aims to Determine how the implementation of strip story media can improve Arabic speaking skills among tenth-grade female students at MA Bajo.and Understand the improvement in speaking skills through strip story media in Arabic learning among tenth-grade female students at MA Bajo. This type of research is classroom action research. The data collection methods are action observation, field notes, test sheets, and documentation. The results of this research are: (1)The classroom action research conducted by the researcher concluded that the improvement in Arabic speaking skills of the tenth-grade students at the Modern Babussa’adah Islamic Boarding School in Bajo can be achieved through the implementation of strip story media.(2) The percentage increase in the first cycle shows that out of 10 students, 8 students completed with a percentage of 80%, while 2 students did not complete with a percentage of 20%. In the second cycle, all students completed, totaling 10 students with a percentage of 100%. From the first cycle to the second cycle, there was an increase in learning outcomes by 20%. Thus, in the second cycle, the learning outcomes are considered complete. ملخص البحث أهداف البحث هي (1) معرفة كيف تطبيق وسيلة Strip Story لتحسين مهارة الكلام لطالبات الصف العاشر بمعهد باب السعادة الحديث باجو لووو. (2) معرفة كيف تحسين مهارة الكلام من خلال وسيلة Strip Story في تعليم اللغة العربية لطالبات الصف العاشر بمعهد باب السعادة الحديث باجو لووو. نوع البحث المستخدم هو البحث الإجرائي أساليب جمع البيانات هي مراقبة العمل وملاحظة ميدانية وورقة الاختبار متوثيق. نتائج البحث هي (1) نسبة الزيادة في الدورة الأولى يمكن ملاحظة أن من بين 10 طالبات،8 طالبات أكملن النسبة (٪80)، في حين أن طالبتان لم يكمل النسبة (٪20). وفي الوقت نفسه، في الدورة الثانية، أكمل جميع العاشرة الطالبات النسبة المئوية (۱۰۰٪). ومن الدورة الأولى إلى الدورة الثانية حدثت زيادة في نتائج التعليم بنسبة (٪20). وهكذا، في الدورة الثانية يقال أن نتائج التعليم قد اكتملت.